Molecular characterization of Listeria monocytogenes isolated from animal products in a city of Northern Brazil - Monteiro,Lilyan Rosmery Luizaga de (2013)
Listeria monocytogenes, a foodborne pathogen causes listeriosis, a fatal disease in about 30% of cases that affects mainly immunocompromised persons. The aim of this research was to characterize L. monocytogenes pulsed-field gel electrophoresis (PFGE) types isolated from meat products collected at public markets in Araguaina city, TO. Sixty samples of raw ground beef and frescal sausage were analyzed during the second half of 2008. Five out of 30 samples (16.7%) of raw ground beef tested positive for L. monocytogenes, three of which were classified as serotype 1/2b and two as serotype 4b. Among the 30 samples of sausage collected, two strains of L. monocytogenes were isolated (6.7%), one of them belonging to serotype 1/2a and the other belonging to serotype 1/2b. The restriction enzymes used were ApaI and SmaI. Similarities among the strains were determined by Dice coefficient. The macro restriction profile obtained by using SmaI enzyme allowed the distribution of seven strains in two clusters, two pulsotypes and two subtypes. The result indicates that L. monocytogenes isolates, belonging to serotype 4b, 1/2a and 1/2b, are strongly correlated within the same serotype group, and in some cases among different serotypes, suggesting that they have a common source.